A Novel Method for Node Fault Detection Based on Clustering in Industrial Wireless Sensor Networks. (1st July 2015) - Zhang, Wenbo; Han, Guangjie; Feng, Yongxin; Cheng, Long; Zhang, Deyu; Tan, Xiaobo; Fu, Lidong
Abstract : Fault detection is a method of crucial importance to guarantee Quality of Service (QoS) in industrial wireless sensor network (IWSN). Timely and accurate detection for fault nodes can increase the robustness of IWSN. Therefore, in order to reduce the network detection load and improve the system scalability, a cluster-based fault detection (CFD) algorithm is proposed. In this algorithm, the IWSN is clustered based on Low Energy Adaptive Clustering Hierarchy (LEACH) protocol at the beginning, and then the reliability of all cluster head nodes is verified. In each cluster, the cluster head is responsible for fault detection in it. In addition, the introduction of node credibility mechanism enables CFD algorithm to tolerate transient faults. Simulation results demonstrate that CFD algorithm has better performances in terms of network energy consumption and detection accuracy.